The study on the relationship between work-life balances towards staff retention at Mextec Corporation (M) Sdn. Bhd. / Rabiatul Asyikin Mohd Lazin - Mohd Lazin, Rabiatul Asyikin (Faculty of Business and Management, 2018)
The study that was conducted was the title were the study on the relationship between work-life balances towards staff retention. In this study, the researcher focused on the relationship between work-life balance at Mextec Corporation (M) Sdn. Bhd and the total questionnaire that had been distributed were 40 set since the population were 45 according to Krejie and Morgan sample size and also using the simple random techniques. The data that had been collected will be analyzed using Statiscal Package for Social Science (SPSS). The data analyzed using the SPSS software were further analyzed using the descriptive analysis, normality test, correlation, standard deviation and means.